U.S. policy toward the Korean peninsula - Council on Foreign Relations Independent Task Force on U.S. Policy Toward the Korean Peninsula; Haass, Richard; Pritchard, Charles L; Snyder, Scott 1964-; Tilelli, John H Jr (John Harold) 1941- (New York Council on Foreign Relations, 2010)
This Task Force report comprehensively reviews the situation on the peninsula as well as the options for U.S. policy. It provides a valuable ranking of U.S. interests, and calls for a firm commitment from the Obama administration to seek denuclearization of the Korean peninsula, backed by a combination of sanctions, incentives, and sustained political pressure, in addition to increased efforts to contain proliferation. It notes that China's participation in this effort is vital. Indeed, the report makes clear that any hope of North Korea's dismantling its nuclear program rests on China's willingness to take a strong stance. For denuclearization to proceed, China must acknowledge that the long-term hazard of a nuclear Korea is more perilous to it and the region than the short-term risk of instability. The report also recognizes that robust relations between Washington and its allies in the region, Japan and South Korea, must underpin any efforts to deal with the North Korean problem. It looks as well at regime change and scenarios that could lead to reunification of the peninsula. At the same time that the Task Force emphasizes the danger and urgency of North Korea's behavior, it recognizes and applauds the beneficial U.S. relationship with South Korea, which has proved to be a valuable economic and strategic partner. In this vein, the Task Force advocates continued close coordination with Seoul and urges prompt congressional passage of the U.S.-South Korea free trade agreement
Includes bibliographical references (p. 61-64)
Also available via the Internet
1
Keywords: Nuclear nonproliferation -- Korea (North); Security, International; China -- Military relations; Korea (North) -- Military relations; Korea (South) -- Military relations; United States -- Military policy; United States -- Military relations -- Korea